1986
DOI: 10.1128/jb.166.3.878-883.1986
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of growth and protein secretion defects in Escherichia coli secA mutants by decreasing protein synthesis

Abstract: We devised a new selection for conditionally lethal suppressors of secA mutants. This selection allows the isolation of both temperature-sensitive and cold-sensitive suppressor mutations, whereas previous studies were limited to nonlethal or cold-sensitive suppressor mutations. Two temperature-sensitive suppressor mutations lie in genes required for protein synthesis: asnS, the gene for the asparaginyl-tRNA synthetase, and divE, which encodes the tRNAser. A previously characterized mutation in alaS, the gene f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 35 publications
3
50
1
Order By: Relevance
“…To examine the relationship between translation rate and protein export in different genetic backgrounds, we pulse-labeled MC4100 and HDB55 and monitored OmpA export in the presence of varying concentrations of the peptidyltransferase inhibitor chloramphenicol. Sublethal concentrations of this drug have been shown to suppress export defects caused by mutations in the translocation machinery (38). If disruption of tig reduces the SecB requirement by slowing translation, then OmpA should be exported in HDB55, which contains a threshold concentration of chloramphenicol.…”
Section: Fig 2 Disruption Of Tig Enhances Bla Export In Srp-deficiementioning
confidence: 99%
“…To examine the relationship between translation rate and protein export in different genetic backgrounds, we pulse-labeled MC4100 and HDB55 and monitored OmpA export in the presence of varying concentrations of the peptidyltransferase inhibitor chloramphenicol. Sublethal concentrations of this drug have been shown to suppress export defects caused by mutations in the translocation machinery (38). If disruption of tig reduces the SecB requirement by slowing translation, then OmpA should be exported in HDB55, which contains a threshold concentration of chloramphenicol.…”
Section: Fig 2 Disruption Of Tig Enhances Bla Export In Srp-deficiementioning
confidence: 99%
“…In these experiments we used a strain that contains a secA am mutation and a temperature-sensitive amber suppressor. At low temperature full-length SecA protein is synthesized, but at high temperature only a small unstable fragment of the protein is produced (16 (28). Selective media contained 100 g/ml ampicillin or 40 g/ml chloramphenicol.…”
mentioning
confidence: 99%
“…These suppressor mutations have been located to a surprisingly large number of genes, most of them involved in protein synthesis (9,14,18,20). It has been suggested that most of these suppressors operate indirectly by reducing the rate of protein synthesis, thereby bringing the processes of protein synthesis and secretion back into balance (9,20).…”
mentioning
confidence: 99%
“…It has been suggested that most of these suppressors operate indirectly by reducing the rate of protein synthesis, thereby bringing the processes of protein synthesis and secretion back into balance (9,20). This proposal was also supported by the observation that even low levels of protein synthesis inhibitors such as chloramphenicol suppressed both temperature-sensitive and cold-sensitive sec mutants and resulted in increased rates of protein export under normally nonpermissive conditions (9). One suppressor of the secY24(Ts) mutation ssyB63(Cs) has been shown recently to be an insertional disruption of nusB, a gene important in transcription antitermination and essential for the growth of E. coli at low temperatures (5,12,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation